A high-capacity Li[Ni0.8Co0.06Mn0.14]O2 positive electrode with a dual concentration gradient for next-generation lithium-ion batteries. Issue 44 (2nd October 2015) - Park, Kang-Joon; Lim, Byung-Beom; Choi, Moon-Ho; Jung, Hun-Gi; Sun, Yang-Kook; Haro, Marta; Vicente, Nuria; Bisquert, Juan; Garcia-Belmonte, Germà
Abstract : The high stability of the outer surface composition in dual concentration gradient Li[Ni0.64 Co0.06 Mn0.30 ]O2 is responsible for reduced resistances by decreasing the electrolyte reaction. Abstract : To increase the reversible capacity of layered lithium nickel-cobalt-manganese oxide, a Li[Ni0.8 Co0.06 Mn0.14 ]O2 positive electrode with a two-sloped full concentration gradient (TSFCG) was successfully synthesized via co-precipitation. The TSFCG maximizes the Ni concentration in the particle core and the Mn concentration on the particle surface. The TSFCG Li[Ni0.8 Co0.06 Mn0.14 ]O2 positive electrode showed improved overall electrochemical properties ( i.e., reversible capacity, cycle life, and rate capability) and thermal stability compared to a conventional positive electrode (CC) Li[Ni0.8 Co0.06 Mn0.14 ]O2 without a concentration gradient. Electrochemical impedance spectroscopy showed that the high stability of the outer surface composition of Li[Ni0.64 Co0.06 Mn0.30 ]O2 is responsible for reduction in surface resistance and charge transfer resistance by decreasing the parasitic reaction with the electrolyte. These reduced resistances explain the superior rate capability of TSFCG positive electrodes.